The Cultural Environment Of International Business - David Kenneth; Vern Terpstra (USA South-Western, 1991)
This book provides comprehensive coverage of international business relationships, and goes further to explain how deeply these relationships are affected by cultural differences, such as religious beliefs, values, education, social strata and politics.
Keywords: International business enterprises; Business; Textbooks; Cultural; (CSE3005-N) Concepts and Principles of International Management